2 - La presse écrite à l’épreuve des Droits de l’Homme en Côte d’Ivoire : de l’originelle protection aux paradoxales violations des droits humains - André Banhouman Kamaté (Africa Media Review, 2012)
The press was said to be responsible for serious and massive human rights violations that occurred in Côte d’Ivoire these recent years. Because of its multiple, diverse and sometimes contradictory positions, it was considered either as a support to the ideal quest for the development of populations, or as an opponent, or as a victim of its commitment in favor of human rights. Critics cannot fail to question about the triple status of the press which put in evidence the freedom of expression on the one hand both as an individual human right and a way to protect all the other rights, and on the other hand to protest against violation by and in the press. Thus, it is indispensable to make a critical analysis of the press if we want to bring it back to its original purposes: inform for individual development and the construction of his political consciousness …